Out-of-Pocket Medical Expenditures in the Redesigned Current Population Survey: Evaluating Improvements to Data Processing - Jackson, Heide; Keisler-Starkey, Katherine (Medical care research and review, 2023)
Household surveys are an important source of information on medical spending and burden. We examine how recently implemented post-processing improvements to the Current Population Survey Annual Social and Economic Supplement (CPS ASEC) affected estimates of medical expenditures and medical burden. The revised data extraction and imputation procedures mark the second stage of the CPS ASEC redesign and the beginning of a new time series for studying household medical expenditures. Using data for the calendar year 2017, we find that median family medical expenditures are not statistically different from legacy methods; however, updated processing does significantly reduce the percentage of families estimated to have a high medical burden (medical expenses are at least 10% of family income). The updated processing system also changes the characteristics of families with high medical spending and is primarily driven by changes in imputation of health insurance and medical spending.